Analisa Kebijakan Pemerintah Dalam Bidang Moneter Guna Meningkatkan Kualitas Indeks Harga Saham Gabungan Di Bursa Efek - Panji Pramuditha; Budi Harto (LPPM POLITEKNIK LP3I BANDUNG, 2022)
The JCI is considered as a part of economic development tools that have erratic fluctuations, this uncertainty is stabilized by the monetary policy pursued by the government in which this policy will react to the shift in the JCI towards positive or negative. This monetary policy will regulate, among others, interest rates, inflation, and the money supply. This study aims to determine whether this monetary policy has an impact on the JCI or does not actually have any effect. The method used is descriptive method which describes the condition of the object to be studied. This study shows that a decrease in interest rates has an impact on the JCI and a different effect from the money supply in Indonesia which is considered not to have a significant effect on inflation so that it does not make the JCI experience a shift or change in investor investment patterns.